2015
DOI: 10.1016/j.ophtha.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Imaging of the Optic Nerve and Retina in Optic Nerve Hypoplasia

Abstract: PurposeTo investigate the optic nerve and macular morphology in patients with optic nerve hypoplasia (ONH) using spectral-domain optical coherence tomography (SD OCT).DesignProspective, cross-sectional, observational study.SubjectsA total of 16 participants with ONH (10 female and 6 male; mean age, 17.2 years; 6 bilateral involvement) and 32 gender-, age-, ethnicity-, and refraction-matched healthy controls.MethodsHigh-resolution SD OCT (Copernicus [Optopol Technology S.A., Zawiercie, Poland], 3 μm resolution)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 33 publications
8
68
1
4
Order By: Relevance
“…As subnormal optic disc areas may be undetectable by fundus photography, OCT analysis is essential in the evaluation of optic disc hypoplasia associated with FAS. 21 Pilat et al showed that peripapillary RNFL thickness was homogeneously reduced in patients with optic disc hypoplasia. 21 Our results showed that although RNFL thickness was reduced in FAS patients, this reduction was not homogeneous in the whole peripapillary area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As subnormal optic disc areas may be undetectable by fundus photography, OCT analysis is essential in the evaluation of optic disc hypoplasia associated with FAS. 21 Pilat et al showed that peripapillary RNFL thickness was homogeneously reduced in patients with optic disc hypoplasia. 21 Our results showed that although RNFL thickness was reduced in FAS patients, this reduction was not homogeneous in the whole peripapillary area.…”
Section: Discussionmentioning
confidence: 99%
“…21 Pilat et al showed that peripapillary RNFL thickness was homogeneously reduced in patients with optic disc hypoplasia. 21 Our results showed that although RNFL thickness was reduced in FAS patients, this reduction was not homogeneous in the whole peripapillary area. Sectorial analysis of the peripapillary RNFL per quadrants showed statistical significant differences in the inferior, superior and nasal quadrants, but not in the temporal quadrant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients have bilateral involvement. Close examination of the optic nerves typically reveal a "double-ring" sign where the inner ring corresponds to the hypoplastic nerve and the outer ring corresponds to the junction between the sclera and lamina cribrosa [1]. Superior segmental optic nerve hypoplasia (SSOH) is a subcategory of optic nerve hypoplasia and is also known as "topless disc syndrome. "…”
Section: Discussionmentioning
confidence: 99%
“…In addition to significantly smaller discs, horizontal cup diameters, and cup depths, some interesting and novel alterations in macular morphology have been characterized, including foveal hypoplasia and thinning of the RNFL, GCL, IPL, ONL, and IS. 95 Optical coherence tomography also can detect RNFL loss from optic atrophy occurring secondary to optic pathway glioma in older children affected by neurofibromatosis type 1. 96 In addition, the potential of the HH-SDOCT to monitor progressive optic neuropathies such as optic nerve glioma in infants and young children unable to cooperate with traditional OCT testing devices has been established.…”
Section: Optic Nerve Pathologymentioning
confidence: 99%